Mesin Diesel Kecepatan Rendah Dua Langkah Dengan Rasio Kompresi 13 dan Rasio Tekanan 1,7 Dengan Penentuan Parameter-Parameter Titik-Titik Utama Siklus Kerjanya (Kajian Teoritis) - Aloysius Eddy Liemena (Industrial Engineering Study Program, Pattimura University, 2012)
An internal-combustion engine is a reciprocating type of engine in which the working substance is a mixture of gases produced by combustion of fuel in the engine cylinder. A diesel or compression-ignition engine is a machine with self-ignition engine of fuel and internal mixing. The working cycle of a diesel engine can also be completed in two strokes of the piston. The mixture of gases produced upon the combustion of the fuel in the cylinder of the engine forms the working substance which presses against the piston and does work. The pressure and temperature at the principal points that characterize the working cycle of a diesel engine can be determined from formulas of thermodynamics with account taken of the thermochemical processes that take place in the engine.